Fallow Weed Control with Preemergence Tank Mixes of Sharpen, Zidua, Sencor, Banvel, Atrazine, Balance Pro, and Corvus - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
With the exception of the tank mix of Sharpen and Sencor, all other tank mixes that provided 100% kochia control 53 days after treatment (DAT) were three-way tank mixes of atrazine herbicide plus, Banvel, and Balance Pro or Zidua. Only two tank mixes provided 98% kochia control 143 DAT. These were also three-way tank mixes of these chemistries. Combinations of Balance Pro and Sencor were needed to provide greater than 93% control of Russian thistle 143 DAT. No tank mix provided good control of Palmer amaranth 143 DAT. However, tank mixes of Sharpen, Sencor, and Zidua provided 84% control 143 DAT. This might provide a foundation for a subsequent postemergence application in a two-pass weed control program.
Keywords: weed science; weed control; fallow; tank mixes; herbicide; Sharpen; Zidua; Sencor; Banvel; atrazine; Balance Pro; Corvus